Primary Cardiac Angiosarcoma: Pericardial Erosion and Disseminated Metastasis in a Young Active Duty Man - Tyler King; William Day; Michael Dore; Joseph An (Annals of Internal Medicine: Clinical Cases)
Primary cardiac tumors are exceedingly rare with a reported prevalence of 0.0017% to 0.028%. Seventy-five percent of these tumors are benign. Of the primary malignant tumors, the most common are sarcomas. Primary cardiac sarcomas are often rapidly progressive and carry a very poor prognosis because of distant metastasis, erosion within the heart, and the development of circulatory obstruction. We describe an unfortunate case of primary cardiac angiosarcoma leading to the death of an otherwise healthy young man.